1996
DOI: 10.1002/j.1550-8528.1996.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Body Image and Depression Among Obese Women With and Without Binge Eating Disorder

Abstract: MITCHELL. Differences in body image and depression among obese women with and without binge eating disorder. Obes Res. 19%;4:431-439.Obese individuals with binge eating disorder (BED) differ from obese non-binge eating (NBE) individuals in a number of clinically relevant ways. This study examined attitudinal responses to various measures of body image in women seeking obesity treatment, by comparing NBE participants (n=80) to those with BED (n=48). It was hypothesized that women with BED would demonstrate grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 52 publications
4
31
1
Order By: Relevance
“…On the SCID-IV, we did not find a higher level of general psychiatric psychopathology among BED. This finding, based on a small number of BED subjects, was contrary to that of other investigators such as Marcus et al, 25 or Mussell et al 26 Wilfley and colleagues 10 did not find Axis I psychopathology to be significantly related to baseline eating disturbance in BED, although Axis II psychopathology was significantly related to more frequent binge eating and greater eating psychopathology; unfortunately we did not study Axis II psychopathology in our sample of subjects. The high prevalence of depression in both BED and NBE is consistent with previous findings of a high lifetime prevalence of major depressive disorder in the extremely obese (29 -51%).…”
Section: Discussioncontrasting
confidence: 99%
“…On the SCID-IV, we did not find a higher level of general psychiatric psychopathology among BED. This finding, based on a small number of BED subjects, was contrary to that of other investigators such as Marcus et al, 25 or Mussell et al 26 Wilfley and colleagues 10 did not find Axis I psychopathology to be significantly related to baseline eating disturbance in BED, although Axis II psychopathology was significantly related to more frequent binge eating and greater eating psychopathology; unfortunately we did not study Axis II psychopathology in our sample of subjects. The high prevalence of depression in both BED and NBE is consistent with previous findings of a high lifetime prevalence of major depressive disorder in the extremely obese (29 -51%).…”
Section: Discussioncontrasting
confidence: 99%
“…In the field of obesity research, findings of associations between the degree of obesity and feeling less attractive have been published [31]. The results of the present study confirm the findings of other investigators [31, 32, 33]that overweight females are less content with or experience less pleasure in their body compared to subjects with normal body weight. They react negatively towards their body and fail to positively identify with it.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous other studies found that binge eaters, compared with nonbinge eaters, reported not only more symptoms of depression, but also lower self-esteem, greater symptoms of borderline personality disorder, and greater lifetime prevalence of any Axis I mental disorder, including substance abuse or dependence. 48,[50][51][52][53][54][55][56] The presence of binge eating, therefore, can be considered a risk factor for depression and various other forms of psychopathology. …”
Section: Binge Eatingmentioning
confidence: 99%
“…Obese bingers reported significantly greater dissatisfaction than did obese nonbingers; the increased dissatisfaction among bingers could not be explained by mood or BMI. 51 Although obese people are more dissatisfied with their bodies than are their average-weight peers, body image dissatisfaction is moderately to strongly associated with greater depressive symptoms and lower self-esteem regardless of weight. 69 The direction of the relationship between body image dissatisfaction and clinically significant depression is unknown.…”
Section: Body Image Dissatisfactionmentioning
confidence: 99%